Reproductive behaviour repertoire of semi-captive lowland tapir Tapirus terrestris (Linnaeus, 1758) - Luisa Brusius; Luiz Carlos Pinheiro Machado Filho; Luiz Gustavo R. Oliveira-Santos; Marcos A. Tortato; Maria J. Hötzel (Biotemas, 2007)
The reproductive behaviour of five male and two female semi-captive Tapirus terrestris was investigated for two years without interruption. They were fenced in a 160 hectare area, in Santa Catarina State, South of Brazil. Data was collected whenever an animal exhibited reproductive behaviour. Seven behaviours, observed in eleven reproductive events, were divided into three categories: courtship, copulation and post-copulation. The tapirs displayed stereotypical patterns of sexual behaviour. No kind of audible vocalization was recorded during the reproductive period. All reproductive activity began in the second quarter of July and continued up to the first half of October, in both years of observation, pointing towards the existence of a reproductive season, corroborated by two births after expected gestation period from copula.